A review of asphalt-filler interaction: Mechanisms, evaluation methods, and influencing factors. (13th September 2021) - Wu, Wangjie; Jiang, Wei; Yuan, Dongdong; Lu, Rong; Shan, Jinhuan; Xiao, Jingjing; Ogbon, Aboudou Wassiou
Graphical abstract: Highlights: A review of the asphalt-filler interaction is presented. Asphalt-filler interaction models and mechanisms were investigated. Critical volume fraction of filler in asphalt mastic was analyzed. Various evaluation methods of asphalt-filler interaction were discussed. Influence factors of asphalt-filler interaction were summarized. Abstract: Asphalt mastic, composed of asphalt and filler, is an important part of asphalt mixture. The interaction between asphalt and filler, called asphalt-filler interaction, directly affects the performance of asphalt mastic and asphalt mixture, because composite materials are more likely to be damaged from the interface. However, how to accurately and effectively measure or evaluate the asphalt-filler interaction has always been an important issue that has not been solved in the field of pavement materials. For better understanding and improving asphalt-filler interaction, this paper reviews existing research on asphalt-filler interaction, including asphalt-filler interaction models and mechanisms, the critical volume of filler in mastic, evaluation methods of asphalt-filler interaction, and influencing factors. From the numerous literature it can be concluded that 1) asphalt-filler interaction is a very complex physicochemical interaction, and current theories cannot fully explain the interaction process; 2) there are five main methods for evaluating asphalt-filler interaction, namely rheological theory, adsorbed asphalt film thickness, surface free energy, atomic force microscopy and molecular dynamics simulation; 3) the main factors influencing the asphalt-filler interaction are the properties of asphalt and filler, as well as external conditions such as temperature, load, and moisture. Besides, the achievements including advantages and disadvantages of each branch have been discussed in different sections, and some improvements are proposed to deepen the mechanism and evaluation methods of asphalt-filler interaction, thus provide references for improving the service life of the asphalt pavement.